The role of sponsorship in shaping integrity in elite sport: perspectives from clean sport advocates - Lebeter, A.; Bond, A. J.; Sparkes, A. C.; Backhouse, S. H. (Qualitative Research in Sport, Exercise and Health, 2026)
This study examines how elite track and field athletes who advocate for clean sport understand the role of sponsorship in shaping integrity within a commercialised sport context. Drawing on an interpretive qualitative approach, we conducted a secondary analysis of 12 publicly available episodes from the Clean Sport Collective podcast, in which athletes reflect on sponsorship, professionalisation, and ethical challenges in elite sport. Using reflexive thematic analysis, four themes were generated: (1) the impact of commercial pressures on athletes` lived experiences, (2) how sponsorship structures shape perceived performance expectations and doping vulnerabilities, (3) the perceived risks and constraints associated with speaking publicly about doping and other integrity-related concerns, and (4) alternative sponsorship models that prioritise athlete wellbeing. Athletes frequently referenced doping as one salient integrity concern, positioning it as a moral and economic injustice that undermines sporting competition, while also expressing concern about reputational and contractual consequences of addressing integrity issues in public forums. Athletes did not describe personal intentions to use prohibited substances; rather, they articulated how commercial and sponsorship environments can create ethical tensions that disproportionately disadvantage those committed to clean sport. Collectively, the findings highlight the vulnerabilities of athletes within elite sport as they navigate sponsorship systems and point to the potential for sponsors to play a more active role in fostering ethical practice and clean sport cultures.